Effect of an RNA interference drug on the synthesis of proprotein convertase subtilisin/kexin type 9 (PCSK9) and the concentration of serum LDL cholesterol in healthy volunteers: a randomised, single-blind, placebo-controlled, phase 1 trial - Fitzgerald, Kevin; Frank-Kamenetsky, Maria; Shulga-Morskaya, Svetlana; Liebow, Abigail; Bettencourt, Brian R; Sutherland, Jessica E; Hutabarat, Renta M; Clausen, Valerie A; Karsten, Verena; Cehelsky, Jeffrey; Nochur, Saraswathy V; Kotelianski, Victor; et al. (The Lancet (British edition), 2014)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to LDL receptors, leading to their degradation. Genetics studies have shown that loss-of-function mutations in PCSK9 result in reduced plasma LDL cholesterol and decreased risk of coronary heart disease. We aimed to investigate the safety and efficacy of ALN-PCS, a small interfering RNA that inhibits PCSK9 synthesis, in healthy volunteers with raised cholesterol who were not on lipid-lowering treatment. We did a randomised, single-blind, placebo-controlled, phase 1 dose-escalation study in healthy adult volunteers with serum LDL cholesterol of 3·00 mmol/L or higher. Participants were randomly assigned in a 3:1 ratio by computer algorithm to receive one dose of intravenous ALN-PCS (with doses ranging from 0·015 to 0·400 mg/kg) or placebo. The primary endpoint was safety and tolerability of ALN-PCS. Secondary endpoints were the pharmacokinetic characteristics of ALN-PCS and its pharmacodynamic effects on PCSK9 and LDL cholesterol. Study participants were masked to treatment assignment. Analysis was per protocol and we used ANCOVA to analyse pharmacodynamic endpoint data. This trial is registered with ClinicalTrials.gov, number NCT01437059. Of 32 participants, 24 were randomly allocated to receive a single dose of ALN-PCS (0·015 mg/kg [n=3], 0·045 mg/kg [n=3], 0·090 mg/kg [n=3], 0·150 mg/kg [n=3], 0·250 mg/kg [n=6], or 0·400 mg/kg [n=6]) and eight to placebo. The proportions of patients affected by treatment-emergent adverse events were similar in the ALN-PCS and placebo groups (19 [79%] vs seven [88%]). ALN-PCS was rapidly distributed, with peak concentration and area under the curve (0 to last measurement) increasing in a roughly dose-proportional way across the dose range tested. In the group given 0·400 mg/kg of ALN-PCS, treatment resulted in a mean 70% reduction in circulating PCSK9 plasma protein (p<0·0001) and a mean 40% reduction in LDL cholesterol from baseline relative to placebo (p<0·0001). Our results suggest that inhibition of PCSK9 synthesis by RNA interference (RNAi) provides a potentially safe mechanism to reduce LDL cholesterol concentration in healthy individuals with raised cholesterol. These results support the further assessment of ALN-PCS in patients with hypercholesterolaemia, including those being treated with statins. This study is the first to show an RNAi drug being used to affect a clinically validated endpoint (ie, LDL cholesterol) in human beings. Alnylam Pharmaceuticals.